Ill Seen, Well Said (On the Uses of Rhetoric in Julius Caesar and Coriolanus) - Brlek, Tomislav (Array, 1998)
Knowledge and mastery of rhetoric played an important social role in Elizabethan England. In two of Shakespeare's plays studied here, Julius Caesar and Coriolanus, various aspects of (ab)uses of rhetorical skills come to the fore. Problems such as whether the nature of language is contingent or essential are seen to be entangled in the events staged and crucial for understanding the predicament of certain dramatic characters.